2006
DOI: 10.1111/j.1365-2133.2006.07182.x
|View full text |Cite
|
Sign up to set email alerts
|

Instrument-, age- and site-dependent variations of dermoscopic patterns of congenital melanocytic naevi: a multicentre study

Abstract: Because definite clinical and histological criteria for the diagnosis of the congenital nature of naevi are lacking, the use of dermoscopy can be of great help in identifying those lesions where the presence of specific dermoscopic features makes the diagnosis of CN more likely. Moreover, dermoscopy can be useful both for the classification of lesions already identified as congenital according to definite clinical and anamnestic data and for a possible correlation of naevus phenotype and dermoscopic patterns t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
56
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(71 citation statements)
references
References 32 publications
12
56
3
Order By: Relevance
“…The predominant patterns of all melanocytic nevi were globular (50 %), consistent with prior studies [7]. They also observed a reticular pattern among nevi present at birth (28 %), which contradicts previous descriptions of a predominately reticular pattern in CMN for individuals 12 years or older [7,8]. The presence of both globular and reticular patterns in CMN raises questions regarding nevus evolution and pathways responsible for nevogenesis.…”
Section: Congenital Melanocytic Nevicontrasting
confidence: 51%
See 1 more Smart Citation
“…The predominant patterns of all melanocytic nevi were globular (50 %), consistent with prior studies [7]. They also observed a reticular pattern among nevi present at birth (28 %), which contradicts previous descriptions of a predominately reticular pattern in CMN for individuals 12 years or older [7,8]. The presence of both globular and reticular patterns in CMN raises questions regarding nevus evolution and pathways responsible for nevogenesis.…”
Section: Congenital Melanocytic Nevicontrasting
confidence: 51%
“…Results showed no statistical significance between the dermatoscopic features of CMN present at birth and nevi present during the first 2 years of life. The predominant patterns of all melanocytic nevi were globular (50 %), consistent with prior studies [7]. They also observed a reticular pattern among nevi present at birth (28 %), which contradicts previous descriptions of a predominately reticular pattern in CMN for individuals 12 years or older [7,8].…”
Section: Congenital Melanocytic Nevicontrasting
confidence: 51%
“…Many of these structures have been previously described as common features of CMN. [7][8][9]12,15 If the dermoscopic appearance of the lesion revealed that a single pattern was present in greater than one-third of the total area of the lesion, that lesion was classified as having 1 of the following 5 predominant dermoscopic patterns: reticular, globular, reticuloglobular, diffuse background pigment with or without remnant structures, or other. A reticular pattern was defined as a primarily reticular pattern, a globular pattern was defined as a primarily globular pattern, and a reticuloglobular pattern was defined as peripheral reticulation with central globules.…”
Section: Methodsmentioning
confidence: 99%
“…[4][5][6] The identification of distinct dermoscopic features of CMN may provide an important diagnostic tool for distinguishing between CMN and other pigmented lesions. Previous studies [7][8][9] indicate that CMN exhibit distinct dermoscopic features that may be helpful in distinguishing CMN from acquired melanocytic nevi and Becker nevi. There is also evidence that suggests that dermoscopy may be effective in detecting early malignant changes.…”
mentioning
confidence: 99%
See 1 more Smart Citation